Oral dabigatran etexilate versus enoxaparin for venous thromboembolism prevention after total hip arthroplasty: pooled analysis of two phase 3 randomized trials - Eriksson, Bengt; Dahl, Ola E.; Rosencher, Nadia; Clemens, Andreas; Hantel, Stefan; Feuring, Martin; Kreuzer, Jörg; Huo, Michael; Friedman, Richard J. (Thrombosis journal, 2015)
Two phase 3 trials compared 28-35 days of treatment with oral dabigatran 220 mg or 150 mg (RE-NOVATE) or 220 mg (RE-NOVATE II) once daily with subcutaneous enoxaparin 40 mg once daily for prevention of venous thromboembolism (VTE) after elective total hip arthroplasty.
Gesehen am 16.07.2020